PERAN POS BANTUAN HUKUM DI PENGADILAN AGAMA TERHADAP MASYARAKAT MISKIN - Lubis, Fauziah; MTD, Sahman Azhari; Lutfi, Ahmad; Hutagalung, Siti Novika; Irhamni, Ummi; Kartini, Annisa Mutiara (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research aims to analyze the process of providing legal aid and its impact on poor people who file lawsuits in religious courts. The provision of legal aid to poor people who file lawsuits through the legal aid post at the aadama court is one of the efforts to increase access to justice for economically disadvantaged communities. Poor people often do not have the ability to pay court fees and other costs associated with the trial process. To address this problem, various countries have developed legal aid mechanisms for the poor. In Indonesia. Legal aid for the poor can be obtained through legal aid posts in courts, including in religious courts. Using normative juridical research methods, this study found that the provision of legal aid to the poor can increase access to justice and reduce the gap between economically able and economically disadvantaged people. This research also found that legal aid posts in religious courts can be one of the solutions to increase legal awareness and access to justice for the poor.